2019
DOI: 10.1055/a-0810-8533
|View full text |Cite
|
Sign up to set email alerts
|

Late Neutrophil Priming Following a Single Session of High-intensity Interval Exercise

Abstract: This study evaluated the effect of an acute high-intensity interval exercise (HIIE) session on the function of human neutrophils. Twelve sedentary men performed a HIIE session (8 bouts of 60 s at 90% of peak power, intercalated with 75 s of active recovery at 30 W). Neutrophils were collected before, 30 min and 24 h after the exercise session for the evaluation of phagocytic capacity, expression of phagocytic receptors, reactive oxygen species generation, and redox status. 24 h after the HIIE session, an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 65 publications
0
12
0
1
Order By: Relevance
“…While these matrices possess unique advantages in their own right, such as the ability to measure freely circulating metabolites between tissues as is the case with plasma, they disregard the metabolism of circulating blood cells by nature of their collection methods. As appreciation is growing with respect to blood cell adaptations to exercise (Bizjak et al, 2019;de Oliveira Ottone et al, 2019;Estruel-Amades et al, 2019;Shi et al, 2019;Uchida et al, 2019), whole blood analysis enables a more complete representation of physiology. Furthermore, this sample collection is less labor intensive than serum or plasma isolation.…”
Section: Discussionmentioning
confidence: 99%
“…While these matrices possess unique advantages in their own right, such as the ability to measure freely circulating metabolites between tissues as is the case with plasma, they disregard the metabolism of circulating blood cells by nature of their collection methods. As appreciation is growing with respect to blood cell adaptations to exercise (Bizjak et al, 2019;de Oliveira Ottone et al, 2019;Estruel-Amades et al, 2019;Shi et al, 2019;Uchida et al, 2019), whole blood analysis enables a more complete representation of physiology. Furthermore, this sample collection is less labor intensive than serum or plasma isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas neutrophil count increases after an IT session, neutrophil function is transiently reduced in response to in-vitro stimulation [24,25] (Table 1). This functional impairment may be partially explained by the increased release of functionally immature neutrophil from bone marrow or by direct mechanisms such as stress hormones and oxidative stress [24].…”
Section: Discussionmentioning
confidence: 99%
“…One study found mobilization of low differentiated T cells and regulatory T cells (Treg) immediately after HIIT, in parallel with apoptosis of high differentiated T cells three hours after exercise [49]. Two studies verified transitory reduced neutrophil function after SIT [24] and HIIT [25] performance (lasting up to 30 min) in response to in-vitro stimulation (Table 1).…”
Section: Leucocyte Functionmentioning
confidence: 98%
See 2 more Smart Citations